The Role Of Institutional Ownership In Preventing Financial Distress In Technology Companies - Sherly Margaretha; Kazia Laturette (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to examine the effect of profitability ratios and market ratios on financial distress and identify the role of institutional ownership in this relationship in technology companies in Indonesia. This study applies a quantitative method with a sample of 39 technology companies officially recognized on the IDX during the period 2022–2024. The results show that Return on Assets (ROA) has a significant effect on financial distress, while Earnings Per Share (EPS) has a significant negative effect. In addition, institutional ownership was found to moderate the relationship between ROA and EPS on financial distress. These findings emphasize the importance of operational efficiency and institutional oversight in reducing financial risk amid the dynamics of the technology industry. This study presents findings that are relevant to decision makers and market participants in supporting risk management strategies and strengthening corporate financial structures.